WAYS TO INCREASE THE EFFICIENCY OF COMMERCIAL BANK BRANCHES (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes the activities of branches of commercial banks and provides practical recommendations to improve their efficiency.